Ethics and natural resources management: on commons, anti-commons, illegal behavior, and bureaucracy - Coelho, M. P.; Filipe, J. A.; Ferreira, M. A. M. (International Journal of Organizational and Collective Intelligence, 2012)
ABSTRACT This paper proposals are: first, to show how the utilization of common resources can carry important ethical problems; second (and mainly), to stress that the many attempts to solve tragedies in fisheries, by creating interesting projects in aquaculture, are confronted with many obstacles and barriers in the approval process. These obstructions conduct to inefficiencies and carry out also important ethical problems. The Portuguese aquaculture case is used to develop an empirical study on the emergence of an “anticommons tragedy”. The control regime of Common Fisheries Policy is discussed. Ethics and Natural Resources Management: On Commons, Anti-Commons, Illegal Behavior, and Bureaucracy Manuel Pacheco Coelho, SOCIUS, ISEG, University of Lisbon, Lisbon, Portugal José António Filipe, BRU-IUL, Instituto Universitário de Lisboa (ISCTE-IUL), Lisbon, Portugal Manuel Alberto M. Ferreira, BRU-IUL, Instituto Universitário de Lisboa (ISCTE-IUL), Lisbon, Portugal Keywords: Anti-Commons, Aquaculture, Common Fisheries Policy, Ethics, Fisheries.